P274 Cognitive function in idiopathic pulmonary fibrosis. (15th November 2016) - Sharp, C; Adamali, HI; Millar, AB; Dodd, JW
Abstract : Introduction: Patients with Chronic Obstructive Pulmonary Disease (COPD) are known to have cognitive dysfunction and share many co-morbidities with those with Idiopathic Pulmonary Fibrosis (IPF). This led us to hypothesise that patients with IPF may also have cognitive dysfunction. To investigate this, we conducted a prospective, observational study examining cognitive function in IPF patients with normal oxygen saturations, comparing them to COPD and smoking controls. Methods: Patients with IPF and oxygen saturations >88% in room air were recruited from outpatient clinics. Exclusion criteria were dementia, neurological disease and illiteracy. Data from the NOVASC study were used for the COPD and control arms. Pulmonary physiology results and demographic data, including educational and smoking status were collected. Patients completed the Montreal Cognitive Assessment (MoCA) and Hospital Anxiety and Depression Scale (HADS). Group differences were assessed using unpaired t-test, analysis of variance and χ2 test. Multivariable linear regression models were constructed to establish which variables contributed to observed variability in MoCA results. Results: 30 patients with IPF were recruited and were compared to 31 patients with COPD and 26 smoking controls. Results are shown in Table 1 . MoCA scores were lower in both IPF and COPD groups and a greater proportion of IPF patients had scores in the "mild cognitive dysfunction" range of 18–25 (46.7%, compared to COPD 32.3%, control 11.5%, p = 0.018). We also compared the IPF cohort to normative data in a population aged 70–79. The mean MoCA in this population was 27.5 (SD = 5.56, n = 53). The IPF patients had a significantly lower MoCA score (p = 0.035). A multivariable linear regression model including diagnosis, age, education and FVC predicted 18.8% of the variance in MoCA (F (4, 79) = 4.57, p = 0.002). Age was the only significant variable. Conclusions: 46.7% of non-hypoxaemic patients with ILD demonstrate at least mild cognitive dysfunction, some of this can be explained by the effect of age, but compared to published age adjusted normative data, there remains a significant reduction in cognitive function in IPF. This cognitive dysfunction has implications for decision making around treatments in IPF which may have significant side-effects.